Studies on the Mechanism of Action of Nalidixic Acid - Bourguignon, Gerard J. (1973)
With three independent techniques (absorption spectrophotometry, measurement of the deoxyribonucleic acid [DNA] melting temperature, and equilibrium dialysis), no evidence has been found for the binding of nalidixic acid to purified DNA. Also, no evidence has been found to support the hypothesis that nalidixic acid is permanently modified to a new, active compound by the bacterial cell. By using an in vitro DNA replication system developed by Bonhoeffer and colleagues, soluble extracts from nalidixic acid-sensitive cells have been shown to confer nalidixic acid sensitivity on the DNA synthesis of lysates from nalidixic acid-resistant cells. The activity in the extracts is only present in sensitive cells and is nondialyzable and heat sensitive. Finally, two known nalidixic acid-resistant mutants of Escherichia coli, mapping at nal A and nal B, respectively, have been tested to determine whether either of them is a transport mutant. It has been shown that nal B(r) is a transport mutant whereas nal A(r) is not.